STRATEGI PEMASARAN PADA USAHA KOPI KITA DALAM MEMPERTAHANKAN PENJUALAN DI TENGAH PANDEMI COVID-19 - Bei, Florentina; Jamu, Maria Endang (ANALISIS, 2022)
This researcher aims to analyze the sales strategy applied to our coffee company, in the midst of a weakening Indonesian economy due to the Covid-19 pandemic. The method in this research was carried out without a qualitative approach to analyze the marketing strategy applied by the company, KOPI KITA with primary data sources obtained from data collection techniques through interviews, observations, researchers, and a number of related facts. The results are often applied by the company, our coffee during the covid-19 pandemic, the seller experienced the impact of the teacher at the beginning of the outbreak, the covid-19 pandemic due to the lack of people outside the house, but with the benefit of technology and business strategy for people to get better sellers. By reviewing the literature that has been carried out, in order to improve marketing strategies, our KOPI company can apply the SWOT analysis method in increasing sales amidst the COVID-19 pandemic. Key words: marketing strategy, SWOT analysis, KOPI KITA